The Role Of Educators - Rahmadani, Rahmadani; Viona Miftahuljannah; Zulfahmi Lubis (Sean Institute, 2024)
Education plays an important role in building individual character and skills as a foundation for the advancement of society. Educators have a strategic role in character formation and development of students' potential. In Islam, the role of educators is categorized into several aspects, namely as murabbi, nausealim, muaddib, and mudarris. This study discusses the concept of the role of educators in an Islamic perspective based on the hadith and its relevance in modern education. The study method is carried out through analysis of literature and hadith related to the role of educators. The results show that each role has a specific focus, but complements each other to create quality education, covering spiritual, moral, and intellectual aspects so that in modern education, in this case, the role of educators in Islam is very relevant, because it align aspects of education with multidimensional human needs. This study is expected to contribute to the understanding of the importance of the role of educators in the formation of a quality generation.